Ethics in aesthetic space in accommodated language education for adults: representing ethical-affective relations - Hedman, Christina; Adams Lyngbäck, Liz; Paul, Enni; Rosén, Jenny (Scandinavian journal of educational research, 2025)
Drawing from a linguistic ethnographic project in accommodated language education for adult learners with intellectual disability, PTSD or migration stress, this paper engages with the sensing pedagogic body. We explore three language teachers’ recurring physical exercise and relaxation activities in their language courses, including music and images. We expand on previous findings of similar activities in a detailed account of these embodied activities as aesthetic and ethical, breaking with normative temporality and logocentrism, in line with crip theory. Building on both a Levinasian and Deleuzian perspective, we foreground the listening-resonating subject in multisensorial interactions entangled with materialities, and learning as ongoing. The findings contribute new knowledge on the role of aesthetics and relational ethics in this type of embodied space, of relevance to both educational research and practice, in accommodated language education and beyond. The findings also contribute to scholarly debate about representing subjects and subjectivity in linguistic ethnography.